Toxic Trace Elements in Meat and Meat Products Across Asia: A Comprehensive Literature Review and Implications for Human Health - Jose L. Domingo (Foods)
Meat and meat products are vital sources of essential nutrients for human health and development. However, an excessive or inappropriate consumption can pose significant health risks. In 2015, the International Agency for Research on Cancer (IARC) classified red meat as “probably carcinogenic to humans” and processed meat as “carcinogenic to humans”, yet the role of environmental contaminants in these products was not addressed. The present review focuses on human exposure to toxic trace elements (arsenic, cadmium, mercury, and lead) through meat and meat products in Asia, covering scientific literature from 1 January 2000, to 30 August 2024. Based on the citations in PubMed and Scopus databases, Asia is the region with the highest number of reported studies, with China contributing the most data. Concentrations of toxic elements in meat vary significantly depending on animal species, specific tissues consumed, and geographic origin. Correspondingly, estimated daily intakes of toxic elements from meat consumption also differ across studies. While some research highlights negligible carcinogenic and non-carcinogenic risks, others indicate potential health concerns due to elevated toxic element exposure in specific cases. However, similar to observations with organic pollutants, meat and meat products in Asia are not among the primary dietary sources of exposure to toxic elements for humans.